Access to books and English reading: A virtuous circle - Kyung Sook Cho; Stephen Krashen (English Language Teaching and Research Journal (ELTAR-J), 2019)
The hypothesis explored in this paper is whether a “virtuous circle” can be established to promote English language development: providing access to interesting and comprehensible reading material, which in turn will increase reading English books, which in turn will promote English competence and in turn more reading of English books. Specifically, we seek to determine if those with more access to English books at home and through visits to bookstores show more interest in reading, and in turn are more supportive of having an English library at their school.  Analysis of responses of sixth graders at four schools in Korea revealed little access to English reading material, but supported the virtuous circle hypothesis, suggesting that the path to high English competence may be easier to establish than we have imagined.